PERMASALAHAN PEMBELAJARAN DI SEKOLAH DASAR CITRA BAKTI - Fransiska Poang; Antonia Ripo Meo; Dimas Qondias (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study was to determine the learning problems faced at Citra Bakti Elementary School, especially in the implementation of learning media and adaptation to the curriculum used. Citra Bakti elementary school has utilized learning media such as canva and quizziz crated by teachers as an effort to increase student interaction and involoment. However,the results of observations and interviewsshowed that the use of this media has not bee optimal due to various obstacles, such as limitide time, varying understanding of technology among students, in addition, teachers face challenges in implementing the independent learning curriculum, especially in implementing project-based learning methods and contextual approaches that are in accordance with the level of student understanding, there are limited facilities and infrastructure and training for teacher in learning effevtiveness, thus the implementation of the independent curriculum at Citra Bakti Elementary School can be optimized and learning objectives can be achieved effectively.